Psychosocial impact on anophthalmic patients wearing ocular prosthesis - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Bannwart, L. C. [UNESP]; Moreno, A. [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Haddad, M. F. [UNESP]; Dos Santos, E. G. (Elsevier, 2013)
The aim of this study was to assess the improvement in psychosocial awareness of anophthalmic patients wearing ocular prostheses and its relationship with demographic characteristics, factors of loss/treatment, social activity, and relationship between professional and patient. Surveys including a form for evaluation of psychosocial pattern were conducted with 40 anophthalmic patients rehabilitated with ocular prosthesis at the Center of Oral Oncology in the authors' dental school from January 1998 to November 2010. The improvement in psychosocial awareness was assessed by comparing the perception of some feelings reported in the period of eye loss and currently. Wilcoxon tests were applied for comparison of patients' perception between the periods. χ2 tests were used to assess the relationship between the improvement in psychosocial awareness and the variables of the study. In addition, the logistic regression model measured this relationship with the measure of odds ratio. The feelings of shame, shyness, preoccupation with hiding it, sadness, insecurity and fear were significant for improvement in psychosocial awareness. It was concluded that the anophthalmic patients wearing an ocular prosthesis has significant improvement in psychosocial awareness after rehabilitation. © 2012 International Association of Oral and Maxillofacial Surgeons.
Keywords: anophthalmia; artificial eye; maxillofacial prosthesis; quality of life; adaptation; comfort; dental education; fear; human; leisure; patient attitude; shame; social behavior; social psychology; visual prosthesis; Adolescent; Adult; Aged; Aged, 80 and over; Anger; Anophthalmos; Attitude to Health; Child; Educational Status; Emotions; Employment; Eye Diseases; Eye Injuries; Eye, Artificial; Fear; Female; Follow-Up Studies; Humans; Income; Interpersonal Relations; Male; Marital Status; Middle Aged; Professional-Patient Relations; Quality of Life; Self Concept; Shame; Shyness; Young Adult